2010
DOI: 10.1586/ern.10.7
|View full text |Cite
|
Sign up to set email alerts
|

Environmental risk factors in multiple sclerosis

Abstract: The etiology of multiple sclerosis is, at present, not definitely known, but genetic and environmental factors play a role in its causation. Environmental causes have a predominant impact. Epidemiologic research has contributed considerably to the identification of external risk factors in this multifactorial setting, but methodological constraints still play a major part. Viral and other microbial agents have drawn much attention, although none of them is a necessary condition for the disease. This is true al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
53
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 243 publications
0
53
0
4
Order By: Relevance
“…1,2 There is increasing interest in the development of combination therapies, using immune suppressants and drugs with distinct mechanisms of action, but side-effects limit the number of pharmacologic agents that can be safely used. [3][4][5] Combinations of nonpharmaceutical treatments that are known to increase muscle strength and positively influence brain function by multiple mechanisms of action but with minimal side-effects may provide an alternative treatment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 There is increasing interest in the development of combination therapies, using immune suppressants and drugs with distinct mechanisms of action, but side-effects limit the number of pharmacologic agents that can be safely used. [3][4][5] Combinations of nonpharmaceutical treatments that are known to increase muscle strength and positively influence brain function by multiple mechanisms of action but with minimal side-effects may provide an alternative treatment.…”
mentioning
confidence: 99%
“…12,13 The number of mean daily servings of vegetables is inversely correlated with the risk of developing MS and obesity, 14 a common comorbidity. 1 Greens, sulfur-rich vegetables and brightly colored vegetables provide many dietary molecules (e.g., flavonoids, polyphenols, and thiols) with favorable impact on molecular pathways influencing MS disease activity (e.g., sirtuins, adenosine monophosphate protein kinase, nuclear transcription factor j B, and peroxime proliferatoractivated receptors) 12,13 and nutrients important to optimal brain physiology. 11,15,16 Currently, no particular diet is prescribed as a treatment for MS, but some studies suggest that changes in diet might be beneficial.…”
mentioning
confidence: 99%
“…Numerous studies have assessed the associations of different ethnicities and races with the risk of MS worldwide (2,12,14,25). Iran has different ethnic groups, each with specific lifestyle and behavioral habits as well as different environmental exposures.…”
Section: Discussionmentioning
confidence: 99%
“…Despite extensive research, the exact cause of MS is still unknown. Several factors have been reported as risk factors for MS, but the main causes are still unknown (2). Recent studies have indicated the main cause of MS could be a combination of genetic susceptibility and environmental exposures during pregnancy and early puberty.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely accepted that MS is a complex demyelinating disease and both environmental and genetic factors contributed to its susceptibility and progression (Brooks et al, 2010;Lauer, 2010;Libbey et al, 2007;Maya et al, 2008;Sospedra and Martin, 2005;Stridh et al, 2014;Williams et al, 1991;Zivadinov and Pirko, 2012). Environmental factors comprise ethnicity, age, gender, diet, family history, parent-of-origin and so on.…”
mentioning
confidence: 99%